Kemitraan Sekolah Menengah Kejuruan (SMK) Dengan Dunia Usaha/Dunia Industri (DU/DI) Sebagai Implementasi Revitalisasi SMK (Studi Tata Kelola Kemitraan Pada SMK Swasta “DP” Di Jakarta Timur) - Zuhairoh, Nikma; Pattinasarany, Indera Ratna Irawati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to examine the governance and partnership patterns of SMK "DP" with the Business / Industrial World (DU / DI). This partnership is an implementation of Vocational School Revitalization in an effort to increase the competence of graduates and work placements. Based on the theory of sociology, the partnership between SMK and the world of industry / business (DU / DI) can be analyzed using social capital theory according to Coleman. This study uses a qualitative method with a case study approach. The data collection technique is done by observation, in-depth interview (indept interview), and document study. The results of this study indicate that SMK “DP” Jakarta has implemented partnership governance in cooperating with the Business World / Industrial World (DU / DI). This partnership is carried out in collaboration or through the MOU in terms of curriculum validation and synchronization, Field Work Practices (PKL), placement of graduates, vocational competency tests (UKK), job training for productive teachers, the first party Professional Certification Institute (LSP) _P1, and opening industrial vocational class. For SMK, the collaboration carried out is not only to improve the quality of graduates who are ready to work but also as a promotion and selling point of SMK to prospective new students. For the Business World / Industrial World (DU / DI), this partnership is a social contribution and responsibility towards improving the quality of SMK and fulfilling the workforce in accordance with industry needs.